Drosophila DJ-1 mutants show oxidative stress-sensitive locomotive dysfunction. - Park, J.; Kim, S.Y.; Cha, G.H.; Lee, S.B.; Kim, S.; Chung, J. (Gene, 2005)
DJ-1 is linked to an early-onset autosomal recessive Parkinson's disease (PD) characterized primarily by selective loss of dopaminergic (DA) neurons, which results in motor disturbances. However, our understanding on how mutations in DJ-1 are related to PD is unclear. Here, we isolated the DJ-1 orthologue, DJ-1beta, in Drosophila and characterized its expression and loss-of-function mutants. We observed its strongest expression in the adult stage of development and ubiquitous expression in the larval brain. Our homozygous mutants showed severe defects in locomotor ability without loss of DA neurons, consistent with the previous mice DJ-1 mutant studies ([Goldberg, M.S., Pisani, A., Haburcak, M., Vortherms, T.A., Kitada, T., Costa, C., Tong, Y., Martella, G., Tscherter, A., Martins, A., et al., 2005. Nigrostriatal dopaminergic deficits and hypokinesia caused by inactivation of the familial Parkinsonism-linked gene DJ-1. Neuron 45, 489-496.]; [Kim, R.H., Smith, P.D., Aleyasin, H., Hayley, S., Mount, M.P., Pownall, S., Wakeham, A., You-Ten, A.J., Kalia, S.K., Horne, P., Westaway, D., Lozano, A.M., Anisman, H., Park, D.S., Mak, T.W., 2005. Hypersensitivity of DJ-1-deficient mice to 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) and oxidative stress. Proc. Natl. Acad. Sci. USA 102, 5215-5220.]; [Chen, L., Cagniard, B., Mathews, T., Jones, S., Koh, H.C., Ding, Y., Carvey, P.M., Ling, Z., Kang, U.J., Zhuang, X., 2005. Age-dependent motor deficits and dopaminergic dysfunction in DJ-1 null mice. J. Biol. Chem. 280, 21418-21426.]). The locomotor activity of DJ-1beta mutants was further decreased by paraquat-induced oxidative stress. Moreover, we found that Drosophila DJ-1 is prominently localized in mitochondria, suggesting that DJ-1 functions as a protector against oxidative stress in mitochondria.